2022
DOI: 10.1186/s13041-021-00895-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced antinociception to noxious heat requires α1A-adrenaline receptors of spinal inhibitory neurons in mice

Abstract: It is well known that acute exposure to physical stress produces a transient antinociceptive effect (called stress-induced analgesia [SIA]). One proposed mechanism for SIA involves noradrenaline (NA) in the central nervous system. NA has been reported to activate inhibitory neurons in the spinal dorsal horn (SDH), but its in vivo role in SIA remains unknown. In this study, we found that an antinociceptive effect on noxious heat after acute exposure to restraint stress was impaired in mice with a conditional kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, the responsible α 1 -AR subtype for the effect of NA on inhibitory neurons in rats may be different from that in mice. Our previous study using mouse spinal cord slices showed that NA increased the frequency of inhibitory postsynaptic currents in substantia gelatinosa neurons via α 1A -ARs [ 26 , 36 ]. The reason for the difference in the α 1 -AR subtypes involved remains unclear, but some possibilities may be considered: the differences in the species (rat vs. mouse), population of inhibitory interneurons (AAV-NpyP + neurons vs. Vgat-Cre + neurons), and the measured responses (depolarization of cell body vs. inhibitory postsynaptic currents in SDH neurons received inputs from NA-responding neurons).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the responsible α 1 -AR subtype for the effect of NA on inhibitory neurons in rats may be different from that in mice. Our previous study using mouse spinal cord slices showed that NA increased the frequency of inhibitory postsynaptic currents in substantia gelatinosa neurons via α 1A -ARs [ 26 , 36 ]. The reason for the difference in the α 1 -AR subtypes involved remains unclear, but some possibilities may be considered: the differences in the species (rat vs. mouse), population of inhibitory interneurons (AAV-NpyP + neurons vs. Vgat-Cre + neurons), and the measured responses (depolarization of cell body vs. inhibitory postsynaptic currents in SDH neurons received inputs from NA-responding neurons).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that idazoxan reduces the suppressive effect of duloxetine repeatedly administered on neuropathic behavioral hypersensitivity [ 19 ] but not that of acutely administered duloxetine [ 22 ]. In addition to α 2 -AR, NA also activates α 1 -AR and has an excitatory effect on inhibitory interneurons in the SDH [ 23 , 24 , 25 , 26 ]. However, the role of duloxetine in attenuating neuropathic pain-like behavior is poorly understood.…”
Section: Introductionmentioning
confidence: 99%